2020
DOI: 10.5121/sipij.2020.11102
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Decomposition and Alpha Stable Fusion

Abstract: This article gives a new method of fusing multifocal images combining the Laplacian pyramid and the wavelet decomposition using the stable distance alpha as a selection rule. We start by decomposing multifocal images into several pyramid levels, then applying the wavelet decomposition to each level. the originality of this work is to use the stable distance alpha to fuse the wavelet images at each level of the Pyramid. To obtain the final fused image, we reconstructed the combined image at each level of the py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This distance was introduced at the time of the discovery of stable alpha stochastic variables and processes [29], [30]. Several works have shown that working in a stable alpha space can improve the estimation and visibility of certain phenomena whose variability increases significantly [31]- [33]. The alpha-stable distribution is widely used in the processing of impulsive or spiky signals.…”
Section: Introductionmentioning
confidence: 99%
“…This distance was introduced at the time of the discovery of stable alpha stochastic variables and processes [29], [30]. Several works have shown that working in a stable alpha space can improve the estimation and visibility of certain phenomena whose variability increases significantly [31]- [33]. The alpha-stable distribution is widely used in the processing of impulsive or spiky signals.…”
Section: Introductionmentioning
confidence: 99%
“…doi: 10.18178/ijsps.10.4. [18][19][20][21][22][23][24] known that aliasing phenomenon occurs. For more details about aliasing phenomenon, see [28].…”
Section: Introductionmentioning
confidence: 99%